FAITH AND FITNESS: EXAMINING RELIGIOUS ATTITUDES TOWARDS PHYSICAL ACTIVITY IN KERALA (International Journal of Food and Nutritional Sciences, 2022)
In Kerala, where Hinduism, Islam, and Christianity are the dominant faiths, religious beliefs shape individual and collective approaches to physical exercise in unique ways. Religious institutions, including temples, mosques, and churches, serve as community hubs where health initiatives can be integrated to promote physical well-being. However, the religion imposes several limitations on clothes, prayer timing, and doctrine explanation. This becomes a constraint in performing daily exercises. Therefore, health workers have to formulate culture-sensitive intervention activities that help to engage the religious communities into regular physical exercise, respecting the value of the religions. The research article analyses religious beliefs of various religious traditions of physical exercise participation in India among students in Malabar district, Kerala. The sample consisted of 610 participants, aged between 14 and 19 years, comprising 353 Hindus, 143 Muslims, and 114 Christians. The Attitudes towards Physical Activity Scale (ATPAS) was used to assess attitudes, and data analysis was conducted using SPSS software. Statistical techniques, including descriptive analysis and one-way ANOVA, were employed to examine variations in attitudes towards physical activity across religious groups. Results indicated a difference between religious groups on attitudes towards Social Experience, Health and Fitness, Risks, Thrill and Excitement, Aesthetic Experience, Catharsis, and Ascetic Experience at p < 0.01. Hindus and Christians showed higher levels in attitudes towards physical activity than Muslims. These results point to the necessity of targeted strategies for promoting physical activity that take into account religious and cultural contexts to promote healthy practices in an inclusive manner.